The Pumilio RNA‐binding protein APUM24 regulates seed maturation by fine‐tuning the BPM‐WRI1 module in Arabidopsis. Issue 7 (2nd June 2021) - Huang, Ruihua; Liu, Mengling; Gong, Guanping; Wu, Pingzhi; Patra, Barunava; Yuan, Ling; Qin, Hongting; Wang, Xiaoxu; Wang, Guohe; Liao, Huimei; Gao, Lu; Yang, Chengwei; et al.
Abstract: Pumilio RNA‐binding proteins participate in messenger RNA (mRNA) degradation and translational repression, but their roles in plant development are largely unclear. Here, we show that Arabidopsis PUMILIO PROTEIN24 (APUM24), an atypical Pumilio‐homology domain‐containing protein, plays an important part in regulating seed maturation, a major stage of plant development. APUM24 is strongly expressed in maturing seeds. Reducing APUM24 expression resulted in abnormal seed maturation, wrinkled seeds, and lower seed oil contents, and APUM24 knockdown resulted in lower levels of WRINKLED 1 (WRI1), a key transcription factor controlling seed oil accumulation, and lower expression of WRI1 target genes. APUM24 reduces the mRNA stability of BTB/POZMATH ( BPM ) family genes, thus decreasing BPM protein levels. BPM is responsible for the 26S proteasome‐mediated degradation of WRI1 and has important functions in plant growth and development. The 3′ untranslated regions of BPM family genes contain putative Pumilio response elements (PREs), which are bound by APUM24. Reduced BPM or increased WRI1 expression rescued the deficient seed maturation of apum24‐2 knockdown mutants, and APUM24 overexpression resulted in increased seed size and weight. Therefore, APUM24 is crucial to seed maturation through its action as a positive regulator fine‐tuning the BPM‐WRI1 module, making APUM24 a promising target for breeding strategies to increase crop yields. Abstract : APUM24 regulates seed maturation through inhibiting the mRNA stability and translation of CULLIN3‐based E3 ligase adaptor BTB/POZMATH family genes, which regulate the stability of the key seed‐oil regulatory factor WRINKLED 1.